Factors influencing rate of gain, quantity of feed consumed and carcass grade. - Bell, F.W.; Mackintosh, D.L.; Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
The two lots in this trial were selected from 75 range-bred heifer calves purchased in November, 1946 for feeding tests at this station. These calves were a uniform group classified as good to choice feeder calves. The 10 calves in Lot 1 were selected as the probable poorer gainers, and the 10 calves in Lot 2 as the probable better gainers. The sort was made on the evidences of probable gains as indicated by body capacity, chest room, muscling, bone and general appearance. Sorting on the basis of these characteristics resulted in heaver average initial weight of the calves in Lot 2. The calves also were graded individually by using a standard feeder chart. Lot 1 graded average good, and Lot 2 low choice.
Keywords: Beef; Rate of gain; Feed consumption; Carcass grade